Molecular characterization of Portuguese patients with dilated cardiomyopathy - Sousa, Alexandra (2019)
Introduction: Dilated cardiomyopathy (DCM) is a disease of the heart muscle characterized by ventricular dilatation and impaired systolic function. Familial forms account for 30-50% of cases. Autosomal dominant inheritance is the predominant pattern of transmission. Causal genetic variants have been identified in several genes and molecular diagnosis has implications for genetic counseling and risk stratification. Objective: We aimed to estimate the frequency of genetic variants and the molecular basis of DCM in Portugal. Methods: We performed a multicenter study of unrelated patients, recruited between 2013 and 2014. Variants in 15 genes were screened using PCR with direct sequencing (next-generation sequencing with at least 30-fold coverage combined with Sanger sequencing). Results: A total of 107 patients were included, 64 (60%) men, mean age at diagnosis 38±13 years, with 48 (45%) familial cases. In total, 31 rare variants in eight genes (mainly in MYBPC3, TNNT2 and LMNA) were identified, in 28 patients (26%). Only four variants had been previously described in association with DCM, 11 with hypertrophic cardiomyopathy, and nine variants were novel. Four variants were likely pathogenic and the remainder were of uncertain significance. We found no major differences in the main clinical and imaging characteristics between patients with or without rare variants and patients with likely pathogenic variants. Conclusions: Our results reflect the complexity and diversity of DCM genetics. For better inter-pretation of the pathogenicity of the variants found and their causative roles in DCM, molecularcascade screening of families is imperative. Further insight into genotype-phenotype correla-tions and risk stratification is desirable.